Through-ice AUV deployment: Operational and technical experience from two seasons of Arctic fieldwork - Doble, MJ; Alexander Forrest; Wadhams, P; Laval, BE (2009)
Detailed sea ice draft mapping was recently accomplished in the Beaufort Sea, north of Alaska, in 2007 and in the Lincoln Sea, north of Canada's Ellesmere Island, in 2008 using a small (3Â m long, 20Â cm diameter), man-handleable Gavia AUV incorporating an inertial navigation system and a 500Â kHz phase-measuring swath sonar. The topography of specific ice features was mapped across 80Â m-wide swaths by performing repeated runs in the vicinity of access holes drilled in the sea ice. The paper discusses the technical and operational developments undertaken to successfully accomplish the missions, including test deployments in a frozen Canadian lake prior to each Arctic deployment. Example data are shown and accuracy issues discussed. Â© 2008 Elsevier B.V. All rights reserved.